2015
DOI: 10.1186/s12913-015-0713-7
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of contextual elements in implementation: an ethnographic case study

Abstract: BackgroundContextual elements have significant impact on uptake of health care innovations. While existing conceptual frameworks in implementation science suggest contextual elements interact with each other, little research has described how this might look in practice. To bridge this gap, this study identifies the interconnected patterns among contextual elements that influence uptake of an anticoagulation clinic improvement initiative.MethodsWe completed 51 semi-structured interviews and ethnographic observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
1
43
0
1
Order By: Relevance
“…Some studies attempted to define context within a hierarchy of factors [47,54,58,71]. Others made a clear distinction between local contexts (as the implementation setting) and the broader contextual landscape [43]; for example, one study identified three distinct types of context-the setting of care context, the project-specific context and the wider general QI and implementation (QI&I) context [64].…”
Section: Representations Of Context Within Improvement Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies attempted to define context within a hierarchy of factors [47,54,58,71]. Others made a clear distinction between local contexts (as the implementation setting) and the broader contextual landscape [43]; for example, one study identified three distinct types of context-the setting of care context, the project-specific context and the wider general QI and implementation (QI&I) context [64].…”
Section: Representations Of Context Within Improvement Settingsmentioning
confidence: 99%
“…Awareness of the potential impact of implementation contexts and local conditions featured widely in the literature in a range of forms. Context was described both in negative and positive terms: frequently contextual factors were portrayed as barriers and/or facilitators [46-48, 50, 69], and in one instance, context was viewed as a continuum of conditions from positive/favourable/ strong influences to negative/unfavourable/weak influences [58]. Interrelationships among contextual elements acted as barriers to uptake at some sites and as facilitators at other sites, and as such were a predictor of intervention uptake [58].…”
Section: Representations Of Context Within Improvement Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…), which in turn informed the intervention we eventually developed to improve the organization and management of anticoagulation care (McCullough et al. ). The main results of this implementation study are forthcoming.…”
Section: Place In the Research “Pipeline”mentioning
confidence: 99%
“…When comparing Department A and C and their mixed progress, a case emerges for arguing that contextual readiness seems to be the strongest influencing factor. McCullough et al [24] suggest that a department needs 'at least one and possibly two contextual elements to be strong (such as leadership, teamwork or communication) for uptake to occur. If a site was relatively weak in all three of these, uptake would not occur, despite a strong belief in the evidence.…”
Section: Discussionmentioning
confidence: 99%